All Days 2010
DOI: 10.2118/127391-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Surfactant IFT and Polymer Viscosity for Surfactant-Polymer Flooding in Heterogeneous Formations

Abstract: Surfactant Polymer flooding (SP flooding) has drawn more attention than Alkaline Surfactant Polymer flooding (ASP flooding) in China due to the difficulty of demulsification and the scale formation problem from the alkali in ASP. Traditionally, the primary requirement for the surfactant in SP flooding is the lowest interfacial tension (IFT). However, core flooding tests performed in a series of heterogeneous models have demonstrated there exist optimized surfactant IFT and polymer viscosity for SP flooding, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The mobility control should be given priority rather than lowering IFT. This conclusion was in agreement with literatures (Hou, 2004;Lu et al, 2006) It should be noted that both these two literatures Wang et al, 2010) used three layer heterogeneous compacted cementation slabs also known as artificial cores in chemical flooding tests, however, viscosity of ASP or SP in these two tests were apparent viscosity rather than effective viscosity in porous media. The relative permeability change due to capillary number increase, as indicated in literature (Kalaydijan, 1992), and the capillary number difference caused displacement difference and viscous fingerings (Pavone, 1992), may account for the CDC difference.…”
Section: New Cdc Curvesupporting
confidence: 92%
See 2 more Smart Citations
“…The mobility control should be given priority rather than lowering IFT. This conclusion was in agreement with literatures (Hou, 2004;Lu et al, 2006) It should be noted that both these two literatures Wang et al, 2010) used three layer heterogeneous compacted cementation slabs also known as artificial cores in chemical flooding tests, however, viscosity of ASP or SP in these two tests were apparent viscosity rather than effective viscosity in porous media. The relative permeability change due to capillary number increase, as indicated in literature (Kalaydijan, 1992), and the capillary number difference caused displacement difference and viscous fingerings (Pavone, 1992), may account for the CDC difference.…”
Section: New Cdc Curvesupporting
confidence: 92%
“…Strongly water-wet 10 -5 Strongly oil-wet 10 -4 Intermediate 10 -4 to 10 -5 Mixed bimodal, 10 -5 /10 -6 Entrapment Strongly water-wet 10 -5 Baker Dolomlte Water-wet 10 -5 Caddo Limesione(Vugular) Mobilization Water-wet 10 -6 to 10 -7 Entrapment Water-wet 10 -6 to 10 -7 Classic CDC was based on Newton fluid, while non-Newton fluild like polymer fluid was adopted in test recently (Wenxiang et al, 2007;Wang et al, 2010). Literature (Wenxiang et al, 2007) reported viscoelasticity affected CDC with artificial core models and ASP solution.…”
Section: Sandstone Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfactant formulation used in adsorption and oil-recovery experiments is similar to formulations described by other research-ers (Levitt et al 2006;Liu et al 2008;Zhao et al 2008). A blend of A7PS as the major component with a minor amount of a C15-18 IOS gives a blend with high activity and high tolerance to divalent cations.…”
Section: Methodsmentioning
confidence: 99%
“…However, this cEOR technique was mostly carried out in sandstone reservoirs for producing medium and light oils (Wang et al 2010). From the review of Alvarado and Manrique 2010, it was seen that out of the 1507 international EOR projects; most applications were in sandstone reservoirs.…”
Section: Alkali-surfactant Floodingmentioning
confidence: 99%